COGNITIVE INTERPRETATION OF WORD MEANING IN ENGLISH AND UZBEK (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article presents a comparative analysis of the cognitive interpretation of word meaning in English and Uzbek. Drawing on the theoretical framework of cognitive linguistics, the study explores the role of human cognition, conceptual systems, and cultural factors in the formation of lexical meaning. Examples from both languages illustrate how conceptual metaphor, prototypicality, and mental models contribute to meaning construction.
Keywords: cognitive linguistics, word meaning, concept, metaphor, English, Uzbek